The Mirroure of the Worlde : a Middle English Translation of the Miroir de Monde. - Raymo, Robert R. (Medieval Academy books., 2003)
Makes available for the first time the unique text in the fifteenth-century British manuscript, MS. Bodley 283, which is among the last and largest works in the tradition of lay religious instruction mandated by the Fourth Lateran Council.